2004
DOI: 10.1162/1054746042545274
|View full text |Cite
|
Sign up to set email alerts
|

Postural Responses to Two Technologies for Generating Optical Flow

Abstract: The perception and control of stance are frequently studied in virtual environments, where computer-generated videographic displays are used to simulate the optical consequences of body sway. Generally, the intent of such studies is to understand how posture is controlled outside of virtual environments (i.e., in daily life). Accordingly, the validity of such studies will depend upon the extent to which postural responses to videographically generated optical flow resemble postural responses to optical flow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…1 Subsequently, Cunningham et al (2006) used a large FOV virtual display (220º horizontal 50º vertical) to test postural responses to a swinging room while varying the room oscillation amplitude. In contrast to Stoffregen et al (2004), they found a clear increase in body sway with increasing room oscillation amplitude. There are, however, multiple differences that could account for the discrepant results.…”
Section: Postural Control In Virtual Realitymentioning
confidence: 58%
See 4 more Smart Citations
“…1 Subsequently, Cunningham et al (2006) used a large FOV virtual display (220º horizontal 50º vertical) to test postural responses to a swinging room while varying the room oscillation amplitude. In contrast to Stoffregen et al (2004), they found a clear increase in body sway with increasing room oscillation amplitude. There are, however, multiple differences that could account for the discrepant results.…”
Section: Postural Control In Virtual Realitymentioning
confidence: 58%
“…It is often assumed in these experiments that any variable affecting postural control in virtual reality (VR) would have a similar effect if implemented in a real environment (but for exceptions, see Cunningham et al, 2006;Stoffregen, Bardy, Merhi, & Oullier, 2004). However, visual stimulation in virtual displays can differ in potentially important ways from real-world viewing.…”
Section: Postural Control In Virtual Realitymentioning
confidence: 99%
See 3 more Smart Citations